Nitric Oxide Synthases and Atrial Fibrillation - Bonilla, Ingrid M.; Sridhar, Arun; Gyorke, Sandor; Cardounel, Arturo J.; Carnes, Cynthia A. (Frontiers in Physiology, 2012)
Oxidative stress has been implicated in the pathogenesis of atrial fibrillation. There are multiple systems in the myocardium which contribute to redox homeostasis, and loss of homeostasis can result in oxidative stress. Potential sources of oxidants include nitric oxide synthases, which normally produce nitric oxide in the heart. Two nitric oxide synthase isoforms (1 and 3) are normally expressed in the heart. During pathologies such as heart failure, there is induction of nitric oxide synthase 2 in multiple cell types in the myocardium. In certain conditions, the NOS enzymes may become uncoupled, shifting from production of nitric oxide to superoxide anion, a potent free radical and oxidant. Multiple lines of evidence suggest a role for nitric oxide synthases in the pathogenesis of atrial fibrillation. Therapeutic approaches to reduce atrial fibrillation by modulation of nitric oxide synthase activity may be beneficial, although further investigation of this strategy is needed.